The effect of land cover on the foraging behavior and pollen in the honey of the giant bee Apis dorsata in Sumatra - Raffiudin, Rika; Dyahastuti, Meis; Nugraha, Rahmia; Sayusti, Tiara; Djuita, Nina Ratna; Suwananda, Erik; Allvioningrum, Vera; Mardhony, Reza; Biagioni, Siria; Setyaningsih, Christina Ani; Prasetyo, Lilik Budi; Priawandiputra, Windra; et al. (Frontiers in Bee Science, 2024)
Introduction Apis dorsata, the common bee pollinator in tropical forests, is experiencing a population decrease due to several anthropogenic factors that lead to land cover changes and habitat loss. Land cover changes may alter their resource supply and foraging behavior. Our study aimed to determine foraging behavior and botanical origin using pollen of A. dorsata honey in two land cover types: plantationdominated landscape (PL) in Kampar (Riau) and forest-agriculture-dominated landscape (FL) in Kerinci (Jambi) Sumatra, Indonesia. Methods We observed two colonies of A. dorsata flight direction and flight activities in each land cover from 9 am–3pm. Honey was harvested from both nests of A. dorsata and the pollen in the honey was analyzed using acetolysis procedure. Vegetation analysis in both locations was conducted based on the flight directions of the giant honey bees. Results The foraging data of A. dorsata showed a difference in the total number of bees between these two land cover types. The number of bees flying out and returning to the nest was higher in Kerinci than in Kampar, while high morning foraging activities were recorded in both land cover types. Furthermore, the foraging activity of the colonies in the PL landscape, i.e., flying out and returning to the nest with and without pollen, decreased at noon. The palynological results of the honey showed that in the PL landscape, pollen diversity was very low and mainly consisted of Elaeis gueneensis pollen (97%). Meanwhile, pollen types and concentrations were much higher in the FL than in the PL. Discussion This result suggests that A. dorsata exhibits a more varied foraging behavior in a diverse and heterogeneous landscape in Kerinci compared to a plantation-dominated habitat in Kampar.